Improving student achievement : reforms that work - Solmon, Lewis C.; Agam, Kimberly Firetag; Schiff, Tamara Wingard, 1963- (Milken Family Foundation series on education policy., 2005)
Improving Student Achievement: Reforms that Work expands on the first volume in the Milken Family Foundation series on education policy, Talented Teachers: The Essential Force for Improving Student Achievement. The series explains to policymakers, parents, business leaders, and teachers the importance of teacher quality in increasing student achievement. This volume is based primarily on the proceedings from the 2004 Milken National Education Conference (NEC), which was held in Washington, D.C., in May 2004.